EFFECT OF TOCOTRIENOL PRETREATMENT ON EX VIVO SUPEROXIDE AND PEROXIDE HANDLING CAPACITIES (SPHC) OF RAT SERUM AND BRAIN - Dasari, Pitchaiah; R., Anandamurali; Nayak, Prasunpriya (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Tocotrienol (TT), a constituent of vitamin E, present only in selected seed oil. Because of the isoprenoid side chain, antioxidant property of tocotrienol is recently highlighted. Application of tocotrienol is also proven to be neuroprotective. The current study was aimed to evaluate the effect of tocotrienol pretreatment on the serum and brain oxidative stress parameters and oxidant handling capacities. Methods: Male albino Wistar rats were treated with tocotrienol (10 mg/day) for two weeks and maintained for the next four weeks. Levels of reduced glutathione and lipid peroxidation and activities of superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase were estimated fortnightly in serum. After sacrifice, oxidative stress parameters were measured in the frontal cortex, temporal cortex, thalamic area, hippocampus and cerebellum. Glutathione-dependent and glutathione-independent superoxide and peroxide handling capacities (SPHC) were calculated for serum and brain regions. Data collected from both the groups are statistically processed with Kruskal-Wallis test and Mann-Whitney pairwise comparisons. Results: Significant impacts of TT treatment have been observed in terms of growth and water intake. Serum SPHC (Glutathione-independent) has been found to be reduced significantly immediately after the TT treatment. Region-specific alterations in oxidative stress parameters have also been observed after 4 w of supplementation. Global reductions in reduced glutathione and lipid peroxidation have been observed in the brain without any alteration in the SPHC. Conclusion: From the results, it can be suggested that the tocotrienol pretreatment possibly be used as neuroprotective measure particularly against oxidative stress. In addition, the antioxidant impacts of TT were found to be maintained for a longer period in brain regions, even though it was not so in the case of serum.